2015
DOI: 10.14411/eje.2015.031
|View full text |Cite
|
Sign up to set email alerts
|

Potential pollinator of Vanda falcata (Orchidaceae): Theretra (Lepidoptera: Sphingidae) hawkmoths are visitors of long spurred orchid

Abstract: Abstract.Vanda falcata is a species of orchid native to China, Korea and Japan. While it is arguably one of the most celebrated orchids in Japan there is no information on its pollinators. Although most species of the subtribe Aeridinae, to which V. falcata belongs, have a short spur, V. falcata has a long spur. The results of the current study provide strong evidence that V. falcata is pollinated by longtongued hawkmoths (Theretra spp.), which indicates that the evolution of long spurs in V. falcata could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Nocturnal hawkmoth pollination has been reported in several species of flowers with long tubes and reproductive organs Orchidaceae (e.g., Habenaria (Xiong et al 2015;Zhang & Gao 2017;Tao et al 2018), Platanthera (Inoue 1983(Inoue , 1985(Inoue , 1986, and Vanda (Suetsugu et al 2015)), Rubiaceae (e.g., Guettarda (Xu et al 2018)), Xanthorrhoeaceae (e.g., Hemerocallis (Hirota et al 2012)), and Zingiberaceae (e.g., Hedychium (Gao et al 2014)). Some hawkmoth-pollinated flowers are also visited by butterflies and settling moths Morinaga et al 2009;Yokota & Yahara 2012;Gao et al 2014;Mizusawa et al 2014;Nakajima et al 2018;Tao et al 2018).…”
Section: Hawkmothsmentioning
confidence: 99%
“…Nocturnal hawkmoth pollination has been reported in several species of flowers with long tubes and reproductive organs Orchidaceae (e.g., Habenaria (Xiong et al 2015;Zhang & Gao 2017;Tao et al 2018), Platanthera (Inoue 1983(Inoue , 1985(Inoue , 1986, and Vanda (Suetsugu et al 2015)), Rubiaceae (e.g., Guettarda (Xu et al 2018)), Xanthorrhoeaceae (e.g., Hemerocallis (Hirota et al 2012)), and Zingiberaceae (e.g., Hedychium (Gao et al 2014)). Some hawkmoth-pollinated flowers are also visited by butterflies and settling moths Morinaga et al 2009;Yokota & Yahara 2012;Gao et al 2014;Mizusawa et al 2014;Nakajima et al 2018;Tao et al 2018).…”
Section: Hawkmothsmentioning
confidence: 99%
“…To overcome this problem, there has been a recent increase in studies using interval photography to observe nocturnal pollinators (e.g. Suetsugu and Tanaka 2013;Suetsugu et al 2015). In the present study, we observed flower visitors to the orchid Platanthera hologlottis (Orchidaceae) throughout the day and night using interval photography.…”
Section: Introductionmentioning
confidence: 96%
“…In such species, using interval photography to observe diurnal and nocturnal flower visitors is useful for identifying the flower visitors (Suetsugu and Tanaka 2013;Suetsugu et al 2015). Furthermore, the experimental approach to reveal the relative contribution of diurnal and nocturnal flower visitors to fruit production and pollinarium removal is useful for gaining knowledge to identify the effective pollinators because the pollination effectiveness of flower visitors can be estimated by measuring paternal (pollen removal) and maternal (producing seeds) perspectives (Schupp et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Mating behaviour occurred at night (Kilaso and Tigvattananont, 2018). The new island Hyles was collected during the day and without light (Tennent and Russell, 2015). The spurge hawk moth Hyles euphorbiae L. (Lepidoptera: sphingidae) are from moderate to large size and the body weight between 0.1 to 7 gram.…”
Section: Introductionmentioning
confidence: 99%
“…Hawkmoth has role in balance ecosystem through floral pollination, the floral member advertises and signal got to pollinator by olfactory neurons in terminal of proboscis which strongly have role in floral diversity by transferring pollen grains (Haverkamp et al, 2016, Heywood et al, 2017. The long tongued moths are adapted for pollination (Suetsugu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%